Jadwiga Schwann and her syndrome - Khalid Al Aboud (Our Dermatology Online, 2011)
Jadwiga Schwann was a dermatologist from Poland. In the 1960s, Schwann reported a rare congenital genodermatosis.This syndrome is characterized by knuckle pads, leukonychia, palmoplanter keratoderma and sensorineural deafness.This report sheds light on Schwann and the syndrome that bears her name.